On the Rediscovery of a Rare Endemic Grass Pseudodanthonia himalaica - Naithani, H. B.; Chandra, Sumer (Indian Forester, 1997)
Pseudodanthonia himalaica(Hook. F.) Bor and Hubbard a rare grass endemic to in small section of North-Western Himalaya has now been rediscovered after a lapse of about one hundred years.